Immigrants’ use of healthcare in their country of origin: the role of social integration, discrimination and parallel use of healthcare systems. - Kemppainen L; Kemppainen T; Skogberg N; Kuusio H; Koponen P (Wiley-Blackwell Publishing Ltd., 2022)
Aims
The objective of this study was to elucidate the utilisation of Russian health care by immigrants of Russian origin living in Finland (cross-border health care). The study examined the association of cross-border health care with social integration and discrimination. Moreover, it studied whether cross-border health care was used as an alternative to the host-country's healthcare system.
Methods
Data from the Finnish Migrant Health and Wellbeing Survey (Maamu) were utilised. The number of respondents of Russian origin was 545. The main analytical method was logistic regression. The outcome variable was based on a survey item on seeking physician's treatment or help abroad during the last 12 months. Social integration was measured multi-dimensionally, and the indicator was extracted by multiple correspondence analysis. Ethical approval for the study was obtained from the Ethical Committee of the Uusimaa Hospital Region.
Results
We found that 15.4% of the respondents had visited a physician in Russia during the last 12 months. 10.4% had experienced discrimination in Finnish health services during their stay in Finland. Stronger social integration predicted less frequent utilisation of cross-border health care. Experiences of discrimination or unfairness were associated with higher odds for seeking cross-border health care. Cross-border health care was typically used in parallel to the Finnish services.
Conclusions
Our findings on integration and discrimination emphasise the importance of general integration policy as well as cultural competence in health care. Parallel use of healthcare systems entails both risks (e.g double medication, problems of follow-up) and opportunities (e.g. sense of agency), which should be further investigated.